Le discours des enseignants sur leurs pratiques professionnelles face à la réussite scolaire des élèves en éducation prioritaire. Le cas des enseignants d’école élémentaire - Caroline Hache (Cahiers de la Recherche sur l'Education et les Savoirs)
Working in Priority Education Areas (PEA), teachers are facing specific professional conditions. PEA missions and objectives are defined by official texts to ensure the success and equality of chances to all pupils. Through time, these texts bring out the teacher’s role as a support to these pupils’ maximum potential abilities. Regarding the whole range of texts, it is always mentioned: “the success of all”. However, since 1999, texts have stated that consideration should be given to pupils who have remarkable results. How do teachers translate these missions into discourse and meaning in their classrooms? How do they act concretely regarding successful pupils? Our national survey among PEA primary school teachers is focused on their professional practices. Among 1720 answers, we bring out that teachers admit having difficulties to evaluate academic success. They attest having numerous professional doubts. Teachers admit that they do not spend a lot of time with “high performance pupils” (HPP) even though they organize specific activities for them. That is why we call them “the left behind”.